The Role of Character Education in Supporting Transformative Education in the Digital Era: A Systematic Review: Peran Pendidikan Karakter dalam Mendukung Pendidikan Transformatif di Era Digital: Sebuah Tinjauan Sistematis - Megawati, Megawati; Prahmana, Rully Charitas Indra (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Character education is an essential element in achieving transformative education, which aims to shape individuals with integrity and the ability to face present and future challenges. This article presents a literature review on the role of character education in supporting transformative education across various levels of formal and non-formal education. Through this study, multiple sources, including journals, books, and research reports, are analyzed to understand the contribution and effectiveness of character education in the learning process. The purpose of this research is to explore the role of character education in supporting transformative education, including understanding its contribution and effectiveness in the learning process. The study also aims to identify challenges encountered in the implementation of character education and recommend strategies to enhance its success. The review findings indicate that character education contributes to shaping students who are not only academically competent but also possess critical thinking skills, empathy, and social awareness. Transformative education emphasizes active student participation, with character education serving as a foundational element that reinforces this engagement. Values such as honesty, responsibility, and cooperation, integrated into the curriculum, have been proven to enhance student motivation and prepare them to become agents of change. However, the implementation of character education faces challenges such as limited resources, variations in value interpretation, and inconsistent policy support. Therefore, the synergy among the government, educators, and the community is necessary to ensure the successful implementation of character education. In conclusion, character education plays a significant role in supporting transformative education, creating students who are competitive, ethical, and positively contribute to society. Further research is needed to develop innovative and practical implementation strategies to overcome existing obstacles.